(untitled) (Texas Journal of Philology, Culture and History, 2026)
This article provides an in-depth study of the ruins of the city of Yerkurgan in the Karshi oasis and the history of ancient Naxhab based on archaeological research. As a result of research that began in Kashkadarya after World War II, the first layers of the city were discovered. Excavations carried out by S. Kabanov in 1946–1948, M. Masson in 1963–1966, and later by R. Sulaymonov and other scientists showed that Yerkurgan was a major cultural and political center from the 7th century BC to the 3rd century AD. During the archaeological research, defensive walls, the governor’s palace, a temple, potters’ and blacksmiths’ quarters, dahmas, and various residential buildings were discovered. The ceramic finds from the excavations were studied in different stages, and their typological characteristics were found to be inextricably linked with the cultural traditions of the Sogdian and Achaemenid periods. It is also noted that the ancient names of the city - Nautaka, Nashebo, Bolo, Naxhab - are recorded in Aramaic and Greek sources. An ancient document found in Afghanistan confirms these ideas. The new period of rise of Naxhab, which began in the 3rd century, the construction of the governor’s palace and temple, the development of pottery centers are highlighted as an important stage in the history of Central Asia. The article is important in reassessing the early civilizational development and cultural heritage of the region